AgNOR quantity in needle biopsy specimens of prostatic adenocarcinomas: correlation with proliferation state, Gleason score, clinical stage, and DNA content. Issue 4 (August 1996) - Trerè, D; Zilbering, A; Dittus, D; Kim, P; Ginsberg, P C; Daskal, I
Abstract : Aims —To define the relation between the quantity of silver stained nucleolar organiser regions (AgNORs) and histological grade, clinical stage, DNA content, and MIB-1 immunostaining in needle biopsy specimens of prostatic adenocarcinomas. Methods —Histological grade was determined according to the Gleason system. AgNOR quantity, DNA content and MIB-1 immunostaining were evaluated by image cytometry on routine histological sections stained with silver, Feulgen reaction and MIB-1 antibody, respectively. Results —The mean AgNOR area increased with increasing Gleason score. A significant difference was found in the AgNOR values between low, intermediate and high grade tumours. Patients with clinically localised tumour (stages A and B) had lower AgNOR values than patients with advanced disease (stages C and D), but the difference in the mean AgNOR values between the two groups was not statistically significant. Non-diploid tumours had a significantly higher mean (SD) AgNOR area than diploid tumours (3.68 (1.04) μm 2 v 2.73 (0.60) μm 2, respectively), while no significant difference was observed in the mean AgNOR values between aneuploid and tetraploid tumours (3.68 (1.04) μm 2 v 3.70 (1.05) μm 2 ). When AgNOR and MIB-1-PI values were compared using linear regression analysis, a highly significant correlation was found. Conclusions —These data demonstrate that AgNOR quantity reflects the proliferative potential of prostatic adenocarcinomas, and is significantly related to histological grade and DNA content. The ease of application on routine sections, maintaining the morphological integrity of the tissue, the ability to evaluate selected histological areas of limited size and objective quantification by image cytometry make the AgNOR method particularly suitable for cell kinetic analysis in prostatic needle biopsy specimens.